Sustainability of biomass-based insulation materials in buildings: Current status in France, end-of-life projections and energy recovery potentials. (March 2022) - Rabbat, Christelle; Awad, Sary; Villot, Audrey; Rollet, Delphine; Andrès, Yves
Abstract: Concerns over climate change have driven the decarbonization of the building sector, the largest energy consumer in France. This consumption is primarily dedicated to heating and cooling. Thermal insulation in construction plays an important role in the minimization of operational energy consumption. Currently, insulation is performed via mineral and fossil-derived materials, which require high manufacturing energy. For this reason, attention has been paid to finding clean and energy-efficient alternatives. Subsequently, biomass-based insulation materials have been identified as low-embodied energy materials that reduce energy use and greenhouse gas emissions. These green and sustainable insulation materials fall in line with the transition in France towards low-carbon and positive-energy buildings. In this respect, research works have mostly focused on renewable biomass resources and wastes, the design and production of insulation materials, the testing of their properties and their installation in buildings; however, few articles have reviewed their durability and end-of-life management. To fit more in the circular bioeconomy concept, light has been shed in this review on the end-of-life of these biomaterials to avoid their landfilling. Therefore, this review provides a state-of-the-art of the different bio-based building products commercialized in France, with a forecast of their volumes and waste deposits by 2050. Furthermore, this study explores waste management strategies, focusing on waste-to-energy routes, which are revealed to be the most promising. The energy recovery from bio-based insulation wastes expected in 2050 saves 4.1 million m 3 of land, 75, 000 tons of fossil fuels and 89 million euros while avoiding the rejection of 312, 771 tCO2eq . Highlights: The end-of-life of bio-based building products in France is a priority. Reuse and recycling are hindered by managerial, legislative and economic barriers. Waste-to-energy (WTE) technologies are the best viable waste management strategy. WTE saves 4.1 million m 3 of land, 75, 000 tons of crude oil and 312, 771 tCO2eq . A net saving of 89 million euros/year could be redirected to WTE implementation.